Television News Translation in the Era of Market-driven Journalism - Tsai, Claire (Meta, 2012)
Translation scholars have discussed the changing role of translation in the transmission of international news information and called for news translators to adapt to such changes. However, the previous discussion has neglected to address the emerging phenomenon of market-driven journalism and its implications for news translation. Ratings-conscious news stations are beginning to revise news agendas and editorial priorities with a view of competing for audiences. Translators who work in newsrooms also assume a role that is traditionally associated with journalists. The rise of market-driven journalism affords scholars the opportunity to consider how the changing ethos of journalism alters news translation strategies. Furthermore, this change forces a rethinking of some earlier assumptions regarding the nature of translation. Although the prevailing trend of market-driven journalism crosses over different media types, this paper primarily centers on the case of television journalism. By examining authentic broadcast news items that were collected from a commercial television news station in Taiwan and interviews with senior TV news translators, this paper unveils a new profile of television news translators in a news ecology that is defined by market values.